Pengaruh Bauran Pemasaran Jasa Terhadap Keputusan Berwisata Pada Taman Hiburan Pantai (THP) Kenjeran Surabaya - Samulana, Vela; Herman; Chasan Azari (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2024)
Traveling decisions for tourists are influenced by various marketing mix factors including Product, Price, Location, Promotion, People, Process, and Physical Evidence. Of these various factors have an important role in improving travel decisions. The problem in this study is the effect of the service marketing mix on travel decisions at the Kenjeran Surabaya Beach Amusement Park (THP) both partially and simultaneously. The purpose of this study was to determine and analyze the effect of the service marketing mix on travel decisions at Kenjeran Surabaya Beach Amusement Park (THP) both partially and simultaneously. The population used in this study were all tourists at Kenjeran Surabaya Beach Amusement Park (THP). The sample used amounted to 96 respondents. This study uses quantitative methods with an associative approach, the sampling technique used is Incidental Sampling. The statistical analysis used in this study is the data instrument test, classical assumption test, multiple linear regression test, hypothesis testing using the t-test, f test, and the coefficient of determination using SPSS 25 for Windows. The results of testing with the t-test and f-test concluded that the variables of Product, Price, Location, Promotion, People, Process, and Physical Evidence simultaneously and partially had a significant effect on travel decisions. The test results with the Coefficient of Determination (R2) using Multiple Regression concluded that the influence of the seven variables, namely Product, Price, Location, Promotion, People, Process, and Physical Evidence was 92.1%.